2017
DOI: 10.1007/s00234-017-1797-z
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of carotid webs

Abstract: Our MR imaging protocol enables an in-depth evaluation of patients with carotid webs: morphology (by MRA), composition (by multi-contrast FSE), and wall dynamics (by cineFSE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…Interobserver agreement for identification of webs on CTA is high with kappa values over 0.90 [2]. Examination of these lesions with vessel wall imaging shows focal vessel wall thickening with a thin fibrous band and no enhancement, plaque hemorrhage or other atherosclerosis-type characteristics [5]. One such example of wall imaging is provided in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver agreement for identification of webs on CTA is high with kappa values over 0.90 [2]. Examination of these lesions with vessel wall imaging shows focal vessel wall thickening with a thin fibrous band and no enhancement, plaque hemorrhage or other atherosclerosis-type characteristics [5]. One such example of wall imaging is provided in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…The particular morphology of CaW leads to blood stasis in the rostral aspect of the lesion, which leads to thrombosis, as previously documented by histology, CTA, and conventional angiography [2,[6][7][8]. Superimposed thrombosis has been reported in 29-40% of patients with CaW-related strokes and leads to cerebral embolism [2,6].…”
Section: Discussionmentioning
confidence: 79%
“…Compared to CTA, magnetic resonance imaging (MRI) may emerge as a reliable tool to diagnose and characterize carotid webs in more detail, detecting smaller lesions as well as evaluating wall composition, biomechanics, and flow dynamics over time. 14 Carotid bulb lesions were evaluated in a study of Afro-Caribbean stroke patients for a 5-year period. 6 In this study, 25 patients were identified by CTA as having atypical FMD of the carotid bulb (CaFMD).…”
Section: Discussionmentioning
confidence: 99%
“…16 Upon treatment with endarterectomy, a carotid web was seen, and histopathology showed smooth muscle with extensive myxoid degenerative changes, as opposed to the medial fibroplasia and loose collagen seen in FMD. 14 Although no studies compare endarterectomy vs stenting for treatment of a carotid web, we can extrapolate the data from carotid stenosis in which minimal risk is associated with carotid stenting using new stent technologies, 17,18 especially if performed after the first week from symptom presentation. 19…”
Section: Figure 3 Digital Subtraction Angiography Of Injections Of Tmentioning
confidence: 99%